Where there's muck there's gold - CGIAR Research Program on Water, Land and Ecosystems (CGIAR Research Program on Water, Land and Ecosystems, 2017)
Facts about Fortifer • It has been demonstrated to be an effective, safe and potentially sought after fertilizer for a wide range of agricultural activities (based on scientific analysis, extensive field trials and farmer engagement). • It is a reliable source of nutrients and organic matter for improving farmer’s soils. • It is a reliable source of nutrients and organic matter for improving farmer’s soils. • It is already approved for use by the Ministry of Food and Agriculture and is a registered trademark in Ghana. • It is produced through a process that safely handles • and disposes of both human waste, collected from both household and public toilets (fecal sludge), and organic waste. • It is enriched with minerals, and is free of live microorganisms (pathogens) that could otherwise cause disease. • Production and sale of Fortifer can be a profitable business. It is now being produced at a large, purpose-built fecal sludge recycling plant in Tema, through a public-private partnership.